2022
DOI: 10.1038/s41586-021-04274-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into inhibitor regulation of the DNA repair protein DNA-PKcs

Abstract: The DNA-dependent protein kinase catalytic subunit (DNA-PKcs) has a central role in non-homologous end joining, one of the two main pathways that detect and repair DNA double-strand breaks (DSBs) in humans1,2. DNA-PKcs is of great importance in repairing pathological DSBs, making DNA-PKcs inhibitors attractive therapeutic agents for cancer in combination with DSB-inducing radiotherapy and chemotherapy3. Many of the selective inhibitors of DNA-PKcs that have been developed exhibit potential as treatment for var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 47 publications
(70 reference statements)
2
33
0
Order By: Relevance
“…We also examined the effect of M3814 treatment on signaling events mediated by other kinases related to DNAPKcs: ATR (CHK1-S345p), ATM (ATM-S1981p), and MTOR (ribosomal protein S6-S235/236p) 40 42 . We found that these phosphorylation events were not obviously affected at the doses used in the above experiments (i.e., 250 nM, 500 nM, and 1000 nM, Supplementary Fig 2a ), which is consistent with the notion that M3814 is a specific inhibitor of DNAPKcs 38 , 39 , and supports the use of the intermediate dose of 500 nM for the below experiments. Finally, we also examined cellular localization of XLF-WT vs. XLF-K160D by immunofluorescence, and found similar staining patterns (i.e., staining in both the nucleus and cytoplasm, Supplementary Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…We also examined the effect of M3814 treatment on signaling events mediated by other kinases related to DNAPKcs: ATR (CHK1-S345p), ATM (ATM-S1981p), and MTOR (ribosomal protein S6-S235/236p) 40 42 . We found that these phosphorylation events were not obviously affected at the doses used in the above experiments (i.e., 250 nM, 500 nM, and 1000 nM, Supplementary Fig 2a ), which is consistent with the notion that M3814 is a specific inhibitor of DNAPKcs 38 , 39 , and supports the use of the intermediate dose of 500 nM for the below experiments. Finally, we also examined cellular localization of XLF-WT vs. XLF-K160D by immunofluorescence, and found similar staining patterns (i.e., staining in both the nucleus and cytoplasm, Supplementary Fig.…”
Section: Resultssupporting
confidence: 88%
“…We then performed similar experiments with inhibition of DNAPKcs kinase activity, which appears to block its dissociation from DNA ends 7 , 8 , 35 37 . To begin with, we interrogated the effect of inhibiting DNAPKcs kinase activity with the small molecule inhibitor M3814 (i.e., Nedisertib) 38 , 39 , and found a concentration dependent decrease in No Indel EJ events in HEK293 (Fig. 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, single particles are boxed out for iterative classification to sort out suitable particles for the final three-dimensional (3D) reconstruction (Cheng et al, 2015;Lyumkis, 2019). The obtained structural details of biological macromolecules at atomic resolution provide valuable information for not only unravelling the fundamental mechanisms of myriad biological processes but also driving the development of drugs for treating diseases caused by the dysfunctional biological macromolecules (Zhu et al, 2018;Han et al, 2022;Liang et al, 2022). Recent technical breakthroughs in single-particle cryo-EM have created a "resolution revolution" in structural biology by circumventing the major challenges faced when using the traditional X-ray crystallography methods (Cheng, 2015;Cheng, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The BBB penetration capabilities are still under investigation (CilinicalTrials.gov Identifier: NCT04555577). Based on the structural interactions between nedisertib and the active site of the DNA-PK, both the quinazoline and morpholino moieties bind into the hydrophobic pocket, while the pyridazine ring rotates to have π-π interactions with the quinazoline plane [ 284 ]. The chloro-fluorobenzene ring in the active site is directed towards the N-lobe, thus potentially allowing radiohalogenation at positions one and three of the ring.…”
Section: Selection Of New Gb Radiopharmaceuticals Targeting the Ddrmentioning
confidence: 99%